JOURNAL OF GOVERNMENT & POLITICS : Collective Identity and Protest Tactics in Yogyakarta Under The Post-Suharto Regime - David Efendi (FISIPOL UMY, 2015)
In response to an uncertain political situation, since 1998, Yogyakartans have engaged in resistance through groups called indigenous organizations.